2019
DOI: 10.1097/aco.0000000000000794
|View full text |Cite
|
Sign up to set email alerts
|

Safety in office-based anesthesia: an updated review of the literature from 2016 to 2019

Abstract: Purpose of review Office-based anesthesia (OBA) is rapidly growing across the world. Availability of less invasive interventions has facilitated the opportunity of offering new procedures in office-based settings to patient populations that would not have been considered in the past. This article provides a practical approach to discuss and analyze newest literature supporting different practices in the field of OBA. In addition, an update of the most recent guidelines and practice management direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The lowest fatality rates are reported with "true" tumescent liposuction in which general anesthesia is not used. Complication rates are decreasing as new technologies emerge, for example, laser liposuction [8]. Gupta et al reviewed procedures across several accredited facilities and found evidence that in-office procedures are a very safe alternative when adequate patient selection is used.…”
Section: Preventionmentioning
confidence: 99%
“…The lowest fatality rates are reported with "true" tumescent liposuction in which general anesthesia is not used. Complication rates are decreasing as new technologies emerge, for example, laser liposuction [8]. Gupta et al reviewed procedures across several accredited facilities and found evidence that in-office procedures are a very safe alternative when adequate patient selection is used.…”
Section: Preventionmentioning
confidence: 99%
“…Previous reviews over the past ten years showed emerging trends towards patient safety in the office-based surgical (OBS) centers and ambulatory surgery centers (ASC) [1][2][3][4][5]. Common OBS procedures at that time included abdominoplasty, orthopedic surgery, plastic surgery, pain management procedures, and dental surgery, with infrequent complications like venous thromboembolism (VTE), hospital admissions, and rarely, death [1,5].…”
Section: Introductionmentioning
confidence: 99%
“…More procedures and increasing number of patients are today undergoing surgical and diagnostic interventions in freestanding ambulatory surgical units [1]. There is an increasing interest not only in moving procedures to ambulatory surgical centres but also further into office-based surgery [2 ▪ ,3 ▪ ] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%